2009
DOI: 10.1088/0957-4484/20/32/325304
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature Ga surface diffusion from focused ion beam milled grooves

Abstract: Ga diffusion from focused ion beam (FIB) milled grooves has been studied using x-ray photoemission electron microscopy (XPEEM) and mirror electron microscopy (MEM). We analyze the surface chemistry of the FIB structures measuring the Ga presence in the top layers of the milled grooves and morphological defects inside the grooves. The Ga is initially strictly confined to the grooves. However, annealing at temperatures as low as 150 degrees C leads to rapid and significant Ga surface diffusion from the FIB struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…2b, the Gadoped cubic LLZO phase forms according to the present XRD results in the bulk of the particles. Ga diffusion into oxides at such low temperatures was also observed by Mikkelsen et al 45 To further identify the impact of Ga-diffusion into the t-Li 7 La 3 Zr 2 O 12 particles on their phase change and sintering characteristics, we turn to dilatometry measurements on pressed ceramic powder green bodies and correlate the observed changes with diffraction results in the given schematics showing the phase evolution and densication over time. Firstly, in agreement with the in situ XRD studies, the dilatometry measurements conrm the phase transformation at around $100 C shown by a starting volume expansion (broad peak at differential dilatometry plots and expansion in relative dilatometry curves at $100 C), see Fig.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…2b, the Gadoped cubic LLZO phase forms according to the present XRD results in the bulk of the particles. Ga diffusion into oxides at such low temperatures was also observed by Mikkelsen et al 45 To further identify the impact of Ga-diffusion into the t-Li 7 La 3 Zr 2 O 12 particles on their phase change and sintering characteristics, we turn to dilatometry measurements on pressed ceramic powder green bodies and correlate the observed changes with diffraction results in the given schematics showing the phase evolution and densication over time. Firstly, in agreement with the in situ XRD studies, the dilatometry measurements conrm the phase transformation at around $100 C shown by a starting volume expansion (broad peak at differential dilatometry plots and expansion in relative dilatometry curves at $100 C), see Fig.…”
Section: Resultsmentioning
confidence: 69%
“…Ga 2 O 3 addition, a series of XRD patterns were recorded for in-situ heated Ga 2 O 3 + t-Li 7 La 3 Zr 2 O 12 powders with respect to post-annealing temperature, seeFigure 2a; here, again, low as ~ 150 o C. This is also a model experiment highlighting the Ga-diffusion to particles that cannot be directly compared to other previous works, as conventionally Ga is already added to the LLZO directly in the first solid state or sol-gel syntheses[30][31][32][33] . Ga diffusion into oxides at such low temperatures was also observed by Mikkelsen et al45 .To further identify the impact of Ga-diffusion into the t-Li 7 La 3 Zr 2 O 12 particles on their phase change and sintering characteristics, we turn to dilatometry measurements on pressed ceramic powder green bodies and correlate the observed changes to diffraction results in the given schematics showing the phase evolution and densification over time. Ga diffusion into oxides at such low temperatures was also observed by Mikkelsen et al45 .To further identify the impact of Ga-diffusion into the t-Li 7 La 3 Zr 2 O 12 particles on their phase change and sintering characteristics, we turn to dilatometry measurements on pressed ceramic powder green bodies and correlate the observed changes to diffraction results in the given schematics showing the phase evolution and densification over time.…”
mentioning
confidence: 66%
“…This difference arises from the altered band alignment and charge transfer owing to the Ga‐ion injection into heterointerfaces. [ 44 ] In addition, the photocurrents of all samples under 532 nm light are obviously higher than those under 405 nm light, which is different from the comparable photocurrents of unpatterned samples. This indicates that the optical resonance of nanoslits strongly enhances the photocurrent at 532 nm incidence, superimposed on the initial response due to the intrinsic absorption of heterostructures.…”
Section: Resultsmentioning
confidence: 82%
“…For patterned WSe 2 /ReS 2 heterostructures, considerable Ga‐ion implantation occurs in the patterned region, which changes n‐type ReS 2 to p‐type or p‐type WSe 2 to p+‐type WSe 2 . [ 44 ] For the No. 1 heterojunction with bottom patterning (Figure 4c), the electron–hole transportation is similar to unpatterned heterojunctions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation